Continuous Development and Cultivation of Soybean as A Result of Multigamma Irradiation through Final Purifying Method - Bartholomeus Pasangka; Irvandi Gorby (Jurnal Penelitian Pendidikan IPA, 2021)
Soybean was the first legumes in Indonesia with production more decreased, while fulfill of public societies were increased. In order that, it was necessary developed and cultivated with technology application. The main problem investigated in this work was the continuous development of Soybean as a result of multi-gamma irradiation on the first year of research. On the second, third, and the fourth year of research, varieties of mutants were purified by carefully selection while growth of plant until to harvest. The selection type was individual selections. In the same time was done multi-locations test. This work obtained five variations of superior varieties of mutant after purifying, which production range about 3.58 -5.12 t/ha, and the total average production about 4.48 t/ha. Range production of initial variety about 1.96-2.61 t/ha and average production of initial (control) soybean about 2.40 t/ha. Percentage rate production of superior selected mutant variety after purifying about 46.47%